ANALISIS FAKTOR RESIKO YANG BERHUBUNGAN DENGAN KEJADIAN KARIES GIGI MOLAR PERTAMA PERMANEN PADA PASIEN POLI GIGI RSUD SEKAYU - Daisy Risviany; Arum Setiawan; Dianita Ekawati (Poltekkes Kemenkes Jambi, 2021)
Background: Indonesia is experiencing one of the problems that need to be considered is health problems, especially dental and oral health problems. Caries is a dental and oral disease that occupies the top position most often suffered by indonesians. Dental caries are the most common problem in the oral cavity. As many as 60-90% of schoolchildren experience caries worldwide. The prevalence of caries in Indonesians with dental and oral problems increased from 23.1% to 25.9%. Method: This research is an analytical survey with Cross Sectional design. The population in this study was children aged 6-12 years who visited the dental poly sekayu hospital in May-June 2021 which amounted to 198 people. The samples in this study are some children aged 6-12 years who visited sekayu hospital dental poly in May-June 2021 and sampling with Simple Random Sampling method. So the large sample in this study was 67 people. Result: The results of the study obtained there is a significant relationship between the knowledge of parents (p value 0,001), the habit of brushing teeth (p value 0,001) and the regularity of dental examinations (p value 0, 000) with the occurrence of The First Permanent Molar Dental Caries in Patients Of Dental Poly Sekayu Hospital. Conclusion: There are 3 factors related to the incidence of dental caries in the first permanent molars in the dental clinic patient at Sekayu Hospital, namely parental knowledge, brushing habits and regularity of dental examinations